ANALISIS PENGARUH LINGKUNGAN KERJA, STRESS KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI PT BAKRIE PIPE INDUSTRIES - Hana Jauharani (2022)
This research uses quantitative methods to the determine effect of the work environment, work stress, and work discipline on employee performance objectively and systematically. This study uses the object of employees of PT Bakrie Pipe Industries. The population used are 156 people with a random sample using the Slovin formula as many as 112 respondents. Data were collected through questionnaires distributed to employees of PT Bakrie Pipe Industries using the Google Form application. Testing of the data in this study using the SmartPLS 3.0 test application. The series of test processes carried out resulted in the conclusion that 1) there was a positive and significant effect of the work environment on employee performance, 2) there was a positive and significant effect of work stress on employee performance, 3) there was a positive and significant effect of work discipline on performance. employees, and 4) there is a positive and significant influence on the work environment, work stress, and work discipline simultaneously on employee performance.